1979
DOI: 10.1073/pnas.76.12.6124
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthesis of human somatotropin analogs.

Abstract: Complementation of the natural NHrterminal 134amino acid fragment of the reduced, carbamoylmethylated human somatotropin with synthetic analogs of COOH-terminal fragments of 57, 42, or 38 amino acids of reduced, carbamoylmethylated human somatotropin has been investigated. It was found that synthetic fragments of 57 and 42 amino acids gave recombinants with full growth-promoting activity, whereas attempts to obtain a recombinant with the synthetic 38-amino acid fragment were unsuccessful. The synthesis of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Plasmin and thrombin were shown to split the same Arg134-Thr135 peptide bond of HGH, thus allowing the isolation of the same 134-residue N-terminal fragment from either digest after reduction and carbamidomethylation of the Cys53-Cys165 disulfide bond of the hormone (Li & Graf, 1974;Graf et al, 1976). In the present study this N-terminal fragment has been shown to interact noncovalently with the 57-residue thrombin fragment of HGH, just like with the 51-residue C-terminal plasmin fragment of HGH (Li & Bewley, 1976) and several 42-57-residue synthetic analogues of this plasmin fragment (Li et al, 1977(Li et al, , 1981Li & Blake, 1979). It may be noted, however, that the recombinant reported in this paper is the first one which contains the full primary structure of HGH with carbamidomethyl groups on the four cysteine residues.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Plasmin and thrombin were shown to split the same Arg134-Thr135 peptide bond of HGH, thus allowing the isolation of the same 134-residue N-terminal fragment from either digest after reduction and carbamidomethylation of the Cys53-Cys165 disulfide bond of the hormone (Li & Graf, 1974;Graf et al, 1976). In the present study this N-terminal fragment has been shown to interact noncovalently with the 57-residue thrombin fragment of HGH, just like with the 51-residue C-terminal plasmin fragment of HGH (Li & Bewley, 1976) and several 42-57-residue synthetic analogues of this plasmin fragment (Li et al, 1977(Li et al, , 1981Li & Blake, 1979). It may be noted, however, that the recombinant reported in this paper is the first one which contains the full primary structure of HGH with carbamidomethyl groups on the four cysteine residues.…”
Section: Discussionmentioning
confidence: 51%
“…The lack of apparent recombination between the HGH and SGH fragments cannot be due to the presence of the blocking groups on Cys164, Cys181, and Cys189 of the SGH fragment, since even the free cysteine-containing derivative was unable to interact with the N-terminal HGH fragment. In addition, the substitution of the same cysteines with alanines in some synthetic analogues of the coresponding HGH fragment did not seem to affect the complementation reaction between the two protions of HGH (Li et al, 1978;Li & Blake, 1979). It is also known from the previous complementation studies that neither the omission of the first 15 N-terminal residues from HGH-(135-191) (Li & Blake, 1979) or the last 4 C-terminal residues from (Li et al, 1981) nor substitutions at positions 153 and 179 of the segment (Li, 1978)] nor the replacement of Met170 with Nle in several synthetic analogues (Li et al, 1978(Li et al, ,1981Li & Blake, 1979) prevented the recombination of these synthetic and natural analogues of the C-terminal plasmin fragment .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This finding is compatible with the experiments of Li and co-workers (4, 5) using synthetic analogs GLUCOSE OXIDATION BY ADIPOSE TISSUE l80r (6) of the C-terminal third of the hGH molecule, in which methionine 170 was substituted with norleucine and the half-cystine residues at positions 165, 182, and 189 with alanine. They found that such synthetic, substituted analogs of sequences 145-191 and 150-191 would complement with S-carbamidomethylated peptide 1-134 derived from plasmin-digested hGH, whereas an analog of the sequence 154-191 would not (4). Whether natural fragments shorter than peptide 146-191 can complement noncovalently with peptide 1-134 remains to be established.…”
Section: Discussionmentioning
confidence: 95%